PERAN NOTARIS DAN PPAT DALAM MENCEGAH TERJADINYA PENYALAHGUNAAN KUASA JUAL UNTUK PENGHINDARAN PAJAK - Yuliana Zamrotul Khusna; Lathifah Hanim (Jurnal Akta, 2017)
Research on "The Role of Notary and PPAT in Preventing the Occurrence of Function of Selling Authority for Tax Evasion" aims to know what can be done Notary and PPAT in facing the problem of tax evasion often done by society by using power of sale.The results of this study can be concluded, that the first power sales serve as the basis for land transactions and / or building that has the potential to be abused to avoid the obligation to pay taxes. Secondly, every transaction on acquisition of land and / or buildings subject to income tax (VAT) and Customs Acquisition Rights to Land and Buildings (BPHTB), efforts to tax evasion in land transactions, particularly the Income Tax (VAT) and Customs Acquisition Rights to Land and building (BPHTB) by making a Power of Sale before a Notary.The author suggests the need for awareness of the importance of tax is expected with a high public awareness, it will minimize tax evasion, the efforts made by the Government party c.q. National Land Agency should be emphasized related to the certainty the existence of the deed of power sold in the manufacture of Sale and Purchase Agreements relied upon registration of transfer of rights over land because factually legal acts often occur in the community, but normatively has not been set definitively linked the lawfulness of the manufacture of the power to sell in order to avoid circumvention of the Income Tax and BPHTB.Keywords: Tre Role of Notary and PPAT, Sell Counsel, Tax